Hubungan Tingkat Religiusitas terhadap Kecemasan Moral dan Alternatif Pembinaan Moral pada Kenakalan Siswa - Rifai Rifai (Sekolah Tinggi Teologi Baptis, Jakarta, 2021)
Teenagers as the successors of the Indonesian people have received high expectations from the community in moral behavior. Various challenges faced by adolescents today can be able to plunge adolescents into immoral behavior. Adolescent moral behavior is based on adolescent moral anxiety, namely the existence of a personal sense of blame every time a teenager commits an offense. Moral anxiety of adolescents is influenced by the level of adolescent religiosity, if adolescents with moderate religiosity tend to have high moral anxiety as well. To get adolescents with good moral religiosity and anxiety need an alternative moral guidance for juvenile delinquency. Alternative moral guidance is carried out through the cultivation of the character of faith and devotion to God who is omnipresent. In addition, it is necessary to involve teachers of Religious Education and Human Rights as counselors and the implementation of scout extracurricular activities that can shape the positive character of students. Abstrak Remaja sebagai penerus bangsa Indonesia telah mendapatkan ekspetaksi tinggi dari masyarakat dalam perilaku bermoral. Berbagai tantangan yang dihadapi remaja saat ini bisa dapat menjerumuskan remaja dalam perilaku tidak bermoral. Perilaku bermoral remaja dilandasi dengan kecemasan moral remaja yakni adanya rasa tertuduh secara pribadi setiap kali remaja melakukan pelanggaran. Kecemasan rmoral remaja dipengaruhi oleh tingkat religiusitas remaja, jika remaja dengan religiusitas sedang cenderung tinggi akan memiliki kecemasan moral yang tinggi pula. Untuk mendapatkan remaja dengan religiusitas dan kecemasan moral yang baik perlu alternatif pembinaan moral terhadap kenakalan remaja. Alternatif pembinaan moral dilaksanakan melalui penanaman karakter keimanan dan ketaqwaan terhadap Tuhan yang mahaesa. Selain itu perlu pelibatan guru Pendidikan Agama dan Budi Pekerti sebagai konselor dan pelaksanaan ekstrakurikuler pramuka yang dapat membentuk karakter positif siswa.